Whose day is it anyway? St. Patrick's Day as a contested performance of national and diasporic Irishness - Marc Scully (2012)
One of the more intriguing aspects of St. Patrick's Day celebrations as a nationalised ritual of a performed Irishness, both within and outside Ireland, is the extent to which it represents a dialogue between territorialised and diasporic expressions of Irish identity, and claims of belonging to Irishness. St. Patrick's Day celebrations in English cities are a particularly intriguing example of this contestation, due to the proximity of the two countries and the historical structural and cultural constraints on the public performance of Irish identity in England, as well as their more recent reinvention within celebratory multiculturalism. This article examines how debates around the authenticity of St. Patrick's Day parades in English cities are employed in the identity work of individual Irish people. In doing so, it provides insight on the tensions between Irishness as transnational, diasporic, and ethnic, as experienced in England.